PLANT PROTEIN SOYBEAN AS SUBSTITUTE OF FISHMEAL IN PRACTICAL DIETS FOR CATFISH CLARIAS BATRACHUS (INDIAN MAGUR) - Rani, Sudesh (Zenodo, 2019)
Plant protein soybean was evaluated as replacements for fish meal in practical diets prepared with 40% crude protein to assess the performance of Clarias batrachus fed different levels. Diets-1-4 contained 65, 130, 195, 260 g kg-1 of raw soybean whereas diets 5-8 contained processed soybean with same level as that of diets- 1-4. Other ingredients like sesame oil cake, rice bran, wheat flour, mineral premix and cod liver oil were also added in diets to fulfill the nutritional requirements. Fish meal (as chief protein source) was used to prepare reference diet (Diet-R). The study was conducted in fresh water in 18 aquariums in duplicates equipped with aeration systems. After 60 days, the weight gain of catfish fed diet-5 (with 65 g kg-1) and diet-6 (with 130 g kg-1) processed soybean was higher than that observed in fish fed on reference as well as diets 1-4 and 8th. Other growth parameters Growth % gain, Specific growth rate (SGR), Viscero somatic index (VSI) and Hepato somatic index (HSI) were also recorded high in diets 5th and 6th. This indicates that soybean meal could be substitute of fishmeal in aquaculture feed. : {"references": ["Agbebi, O., Otubusin, S., & Ogunleye, F. (2009). Effect of different levels of substitution of fishmeal with blood meal in pelleted feeds on catfish Clarias gariepinus (Burchell, 1822) culture in net cages. European", "Antolovi\u0107, N., Ko\u017eul, V., Antolovi\u0107, M., & Bolotin, J. (2012). Effects of partial replacement of fish meal by soybean meal on growth of juvenile saddled bream (Sparidae). Turkish Journal of Fisheries and Aquatic Sciences, 12(2), 247-252.", "Ao, X., Kim, H., Meng, Q., Yan, L., Cho, J., & Kim, I. (2010). Effects of diet complexity and fermented soy protein on growth performance and apparent ileal amino acid digestibility in weanling pigs. Asian-Australasian Journal of Animal Sciences, 23(11), 1496-1502.", "Bairagi, A., Ghosh, K.S., Sen, S. K., & Ray, A. K. (2002). Enzyme producing bacterial flora isolated from fish digestive tracts. Aquaculture International, 10(2), 109-121.", "De Graaf, G., & Janssen, H. (1996). Artificial reproduction and pond rearing of the african catfish Clarias gariepinus in Sub-Saharan Africa. A hanbook: FAO, Roma (Italia).1-73.", "Dubois, M., Gilles, K.A., Hamilton, J.K., Rebers, P.T., & Smith, F. (1956). Colorimetric method for determination of sugars and related substances. Analytical Chemistry, 28(3), 350-356.", "El-Sayed, A.F.M. (2004). Protein nutrition of farmed tilapia: searching for unconventional sources. Paper presented at the New dimensions in farmed tilapia: Proceedings of the Sixth International Symposium on Tilapia, Aquaculture, 392-402.", "FAO. (2012). The state of World Fisheries and Aquaculture FAO Roma, 24-26.", "Gamboa Delgado, J., Rojas-Casas, M.G., Nieto-L\u00f3pez, M. G., & Cruz-Su\u00e1rez, L.E. (2013). Simultaneous estimation of the nutritional contribution of fish meal, soy protein isolate and corn gluten to the growth of Pacific white shrimp (Litopenaeus vannamei) using dual stable isotope analysis. Aquaculture, 380, 33-40.", "Garc\u00eda Ulloa Gomez, M., L\u00f3pez-Aceves, L.A., Ponce-Palafox, J.T., Rodr\u00edguez-Gonz\u00e1lez, H., & Arredondo Figueroa, J.L. (2008). Growth of fresh-water prawn Macrobrachium tenellum (Smith, 1871) juveniles fed isoproteic diets substituting fish meal by soya bean meal. Brazilian Archives of Biology and Technology, 51(1), 57-65.", "Garg, S., Kalla, A., & Bhatnagar, A. (2002). Evaluation of raw and hydrothermically processed leguminous seeds as supplementary feed for the growth of two Indian major carp species. Aquaculture Research, 33(3), 151-163.", "Horwitz, W., Chichilo, P., & Reynolds, H. (1970). Official methods of analysis of the Association of Official Analytical Chemists. Official methods of analysis of the Association of Official Analytical Chemists.1-1015.", "Kikuchi, K., & Furuta, T. (2009). Inclusion of blue mussel extract in diets based on fish and soybean meals for tiger puffer Takifugu rubripes. Fisheries Science, 75(1), 183-189.", "Kruger, J.M., & Osborne, C.A. (1986). Etiopathogenesis of uric acid and ammonium urate uroliths in non-Dalmatian dogs. Veterinary Clinics of North America: Small Animal Practice, 16(1), 87-126.", "Kumar, A. (1984). T. Friedmann: Gene therapy - Fact and fiction. In Biology's New Approaches to Disease Based on the Gene, 29, 355-358.", "Lim, S.J., Kim, S.S., Ko, G.Y., Song, J.W., Oh, D.H., Kim, J.D., Lee, K.J. (2011). Fish meal replacement by soybean meal in diets for Tiger puffer, Takifugu rubripes. Aquaculture, 313(1-4), 165-170.", "Min, B., Cho, J., Chen, Y., Kim, H., Yoo, J., Lee, C., Kim, I. (2009). Effects of fermented soy protein on growth performance and blood protein contents in nursery pigs. Asian-Australasian Journal of Animal Sciences, 22(7), 1038-1042.", "Ogello, E.O., Munguti, J.M., Sakakura, Y., & Hagiwara, A. (2014). Complete replacement of fish meal in the diet of Nile tilapia (Oreochromis niloticus L.) grow-out with alternative protein sources. A review. International Journal of Advanced Research, 2(8), 962-978.", "Olukunle, O., Ogunsanmi, A., Taiwo, V., & Samuel, A. (2002). The nutritional value of cow blood meal and its effects on growth performance, haematology and plasma enzymes of hybrid catfish. African Journal of Online,5(1),22-29.", "Sadasivam, S. (1996). Biochemical Methods: New age international. 2(2), 124-126.", "Sookying, D., & Davis, D.A. (2011). Pond production of Pacific white shrimp (Litopenaeus vannamei) fed high levels of soybean meal in various combinations. Aquaculture, 319(1-2), 141-149.", "Steffens, W. (1989). Principles of Fish Nutrition. Ellis Horwood Limited.1-384.", "Tacon, A.G., & Metian, M. (2008). Global overview on the use of fish meal and fish oil in industrially compounded aquafeeds: Trends and future prospects. Aquaculture, 285(1-4), 146-158.", "Yaghoubi, M., Mozanzadeh, M.T., Marammazi, J.G., Safari, O., & Gisbert, E. (2016). Dietary replacement of fish meal by soy products (soybean meal and isolated soy protein) in silvery-black porgy juveniles (Sparidentex hasta). Aquaculture, 464, 50-59.", "Yigit, M., Erg\u00fcn, S., T\u00fcrker, A., Harmantepe, B., & Erteken, A. (2010). Evaluation of soybean meal as a protein source and its effect on growth and nitrogen utilization of black sea turbot (Psetta maeotica) juveniles. Journal of Marine Science and Technology, 18(5), 682-688.", "Yu, D., Gong, S., Yuan, Y., & Lin, Y. (2013). Effects of replacing fish meal with soybean meal on growth, body composition and digestive enzyme activities of juvenile Chinese sucker, Myxocyprinus asiaticus. Aquaculture Nutrition, 19(1), 84-90.", "Zamani, A., Hajimoradloo, A., Madani, R., & Farhangi, M. (2009). Assessment of digestive enzymes activity during the fry development of the endangered Caspian brown trout Salmo caspius. Journal of Fish Biology, 75(4),932-937."]}